"First of all, Gender is Power": Intersectionality as Praxis in Gender Training. (15th February 2018) - Enderstein, Athena-Maria
ABSTRACT: This paper explores the application of intersectionality in gender+ training. I present findings from research on the translation and transfer of feminist and gender knowledges, drawing from in-depth interviews with gender trainers working in Europe and internationally across private, public and civil society contexts. I outline the use of intersectionality by trainers as a theoretical, analytical and methodological paradigm. These equality actors call for historicization, a recouping of the genealogy of intersectionality and increased attention to the interrelation of systems of power and oppression over time. I apply an emic approach to intersectionality in training scenarios. This is grounded in responsiveness to workshop participants and is supported through affective connection and participatory learning. Dialogue between intersectional subject positions, including that of the trainer, is key to processes of knowledge exchange, reflexivity and social change. Finally, I consider the implications of these insights for engaged pedagogy and transformation oriented praxis.